Restoration prioritization of the Cache La Poudre Watershed - Granau, Lee, author; Fink, Michelle, author; Decker, Karin, author; Sueltenfuss, Jeremy, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2014)
The largest and most destructive fire in the history of Larimer County, the High Park Fire, burned 87,200 acres within the Cache la Poudre watershed with aftereffects including increased flooding, significant erosion, and increased threats to many natural and cultural resources. The natural resources which have been impacted, and will continue to be threatened, include: water used for municipal, domestic, hydropower, and agricultural supply; soil productivity across the forested region; critical habitat for federally listed threated or endangered species; and native plant communities on lands where invasive and noxious species are absent. Currently, restoration work has been completed ad hoc in areas that may not maximize the benefit for the larger public. A comprehensive planning effort was needed to combine stakeholder interests and scientific knowledge to prioritize and maximize future restoration efforts on these publicly owned lands. Our goal was to bring together expert stakeholders to identify the risks and values at risk within the watershed. While this was originally viewed as an activity that would focus solely on the burn area, initial feedback we received suggested we adapt the research to include not only the recently burned area, but the entire watershed, and beyond that, the entire county. As Larimer County had significant interest in our process and provided input to the final model, and to make the results as widely applicable as possible, we decided to use the Larimer County boundary as our research extent. This would allow for the prioritization of restoration activities within the burned area, but also prioritize areas in the Cache la Poudre Watershed and the adjacent Big Thompson Watershed (which was significantly degraded by intense flooding in September 2013). We also adapted the research to include other risks and factors that were not initially included in the post-fire analysis. To accomplish our goal of prioritizing areas across the landscape for restoration activities to reduce risk and increase ecological health, we invited expert stakeholders from local municipalities, the state and federal government, and academic researchers to a workshop for them to provide feedback on risks and values at risk within the watershed.
Prepared for: Laura Jane Musser Fund, Environmental Initiative.
December 2014.
Keywords: wildfire risk; erosion risk; priority treatment areas